The treasures of the pyramids : the world of the pharaohs - Hawass, Zahi A.,; Manferto, Valeria,; Cucchi, Maria,; Accomazzo, Laura,; Ferrero, Giorgio, 1978-, (American University in Cairo Press, 2024)
The pyramids of Egypt are still shrouded in mystery--despite all the research and studies carried out, for example, we still do not know for certain how they were built--but recent excavations and research have thrown new light on these monuments, on the lives of the workers who built them, and on the court dignitaries who were granted the privilege of a burial place near that of their king. Here ... all the most important Old Kingdom pyramids and the great necropolises of Memphis are brought together, examined, and reinterpreted by some of the worlds leading Egyptologists in light of the most recent discoveries.3